Keragaman Serangga Hama Dan Predator Pada Dua Sistem Pertanian Di Pertanaman Kedelai - Susanti, Ambar; Zulfikar, Zulfikar; Yuliana, Anggi Indah; Faizah, Mazidatul; Nasirudin, Mohamad (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2022)
This study provides information about the diversity of pests and predators on organic and non-organic in soybean plantations. This is expected as part of supporting the increase in soybean production in East Java. The diversity of pests and predators are not only influenced by organic or non-organic farming systems, but also on the types of plants being cultivated. Climate also affects the presence of pests and predators. Soybean plants which are included in subtropical plants, when cultivated in a tropical climate, their growth and development are strongly influenced by the tropical climate, which will have an impact on plant resistance to pest attacks. Predators are affected by the presence of pest attacks on their host plants. Meanwhile, the attraction of predators to come to the host plant can be caused by the emergence of volatile compounds released from the saliva of insect pests and also the interaction between these compounds and those released by plants when attacked by pests.